2007
DOI: 10.1038/nsmb1309
|View full text |Cite
|
Sign up to set email alerts
|

Molecular driving forces determining potassium channel slow inactivation

Abstract: K+ channels undergo a time-dependent slow inactivation process that plays a key role in modulating cellular excitability. Here we show that in the prokaryotic proton-gated K+ channel KcsA, the number and strength of hydrogen bonds between residues in the selectivity filter and its adjacent pore helix determine the rate and extent of C-type inactivation. Upon channel activation, the interaction between residues at positions Glu71 and Asp80 promotes filter constriction parallel to the permeation pathway, which a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

20
283
2

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 221 publications
(305 citation statements)
references
References 51 publications
20
283
2
Order By: Relevance
“…The scaffold holding the selectivity filter has long been appreciated for its important role in tuning selectivity in K + channels (7,13). Our results extend this idea in the NaK channel by revealing increased rigidity of the scaffold when the selectivity filter is K + -selective and less rigidity of the scaffold when the selectivity filter is nonselective (Fig.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…The scaffold holding the selectivity filter has long been appreciated for its important role in tuning selectivity in K + channels (7,13). Our results extend this idea in the NaK channel by revealing increased rigidity of the scaffold when the selectivity filter is K + -selective and less rigidity of the scaffold when the selectivity filter is nonselective (Fig.…”
Section: Discussionsupporting
confidence: 78%
“…A structural model for C-type inactivation has been developed for KcsA, with selectivity filter collapse occurring upon channel opening (4)(5)(6)(7)(8)(9)(10). In the reverse pathway, inactivation of the selectivity filter has been linked to changes at the inner gate (5)(6)(7)(8)(9)(10)(11)(12)(13)(14). However, flux-dependent inactivation occurs in Na + and Ca 2+ channels as well and would likely require a structurally different mechanism to explain coupling between the selectivity filter and inner gate (7,(13)(14)(15)(16)(17)(18).…”
mentioning
confidence: 99%
“…This discrepancy between what the crystal structure and the functional data show is explained by the results of Cordero-Morales et al (23) who found that inactivation in KcsA is the result of a conformational change in the selectivity filter region which blocks ion conduction even though the bundle-crossing gate is open. Several features of slow inactivation found in KcsA have counterparts in eukaryotic voltage-gated channels, making the Cordero-Morales explanation a viable one for the molecular basis of slow inactivation in voltage-gated channels (24). Therefore, the most likely functional state that correlates to the crystal structure of both Kv1.2 and the chimera of Kv1.2 with Kv2.1 is the open-inactivated state that has the sensor in the relaxed state, the bundle crossing is in the open state, but the pore is nonconducting because the selectivity filter is in the inactivated state.…”
Section: Discussionmentioning
confidence: 99%
“…In KcsA, the selectivity filter is stabilized by a hydrogen-bond network between E71 and D80, W67 and D80, and a water molecule bound to the backbone nitrogens of G79 and L81 (6). It has been proposed recently that the conformational change in the inner helix during gating propagates to the selectivity filter to trigger the slow inactivation by altering the interaction between E71 and D80 (18). In WSK3, the tertiary contact corresponding to E71 and D80 (E50 and D59) is replaced by a quaternary 3-residue contact among E50 and D59 of one subunit and R68 of the adjacent subunit.…”
Section: Discussionmentioning
confidence: 99%
“…A noteworthy difference between WSK3 and detergentsolubilized KcsA is that in KcsA, the selectivity filter appears as rigid as the TM helices (15), whereas in WSK3, the selectivity filter exhibits relatively higher flexibility. A recent structural analysis of the KcsA slow-inactivation mutants (18) seems to suggest that the selectivity filter is ''intrinsically unstable'' and thus prone to structural rearrangement leading to an inactivated open state. Molecular-dynamics simulations seem to support this conclusion (19).…”
Section: Wsk3 Forms Helical Tetramers In Watermentioning
confidence: 99%